2021
DOI: 10.1097/mog.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and risk factors for pediatric recurrent acute pancreatitis

Abstract: Purpose of review Approximately 20–30% of children who experience one episode of acute pancreatitis will have at least one additional episode. For some children, pancreatitis recurs multiple times and in a few years is followed by the diagnosis of chronic pancreatitis. Identifying risk factors for recurrent episodes and disease progression is critical to developing therapeutic interventions. Recent findings Obesity is driving an increase in biliary ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
4
2
Order By: Relevance
“…The number of drug-related risk factors in the etiological analysis of ARP in this study was higher than that in other studies ( 15 , 16 ), probably because SCMC is one of the largest cancer centers in China, with many hematopathy patients receiving treatment at the center, and because asparaginase is a commonly used chemotherapy drug for acute lymphoblastic leukemia, thus increasing the proportion of cases with drug-induced ARP. Similarly, the number of patients with ARP caused by tumor compression or infiltration increased in the etiology of this study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The number of drug-related risk factors in the etiological analysis of ARP in this study was higher than that in other studies ( 15 , 16 ), probably because SCMC is one of the largest cancer centers in China, with many hematopathy patients receiving treatment at the center, and because asparaginase is a commonly used chemotherapy drug for acute lymphoblastic leukemia, thus increasing the proportion of cases with drug-induced ARP. Similarly, the number of patients with ARP caused by tumor compression or infiltration increased in the etiology of this study.…”
Section: Discussioncontrasting
confidence: 66%
“…The number of drug-related risk factors in the etiological analysis of ARP in this study was higher than that in other studies (15,16), probably because SCMC is one of the largest cancer centers in China, with many hematopathy patients receiving treatment at the center, and because asparaginase is a commonly used chemotherapy drug for acute lymphoblastic leukemia, thus increasing the proportion of cases with druginduced ARP. Similarly, the number of patients with ARP Frontiers in Pediatrics 05 frontiersin.org Comparison of the Kaplan-Meier curves of CP progression between those with (blue) and without (yellow) gene mutations showed a significantly faster rate of progression from ARP to CP (HR of progression was 1.607; 95% CI: 1.024, 2.522; P = 0.039).…”
Section: Discussioncontrasting
confidence: 63%
“…The incidence of childhood obesity continues to rise both in the US and globally [15,16]. Obesity is associated with chronic inflammation, oxidative stress, and more severe AP [17]. Children with obesity are at increased risk of gallstone pancreatitis, and hence cholecystectomy [17].…”
Section: Effect Of Obesity On Pediatric Acute Recurrent Pancreatitis ...mentioning
confidence: 99%
“…Obesity is associated with chronic inflammation, oxidative stress, and more severe AP [17]. Children with obesity are at increased risk of gallstone pancreatitis, and hence cholecystectomy [17]. The International Study Group of Pediatric Pancreatitis in Search For A Cure (INSPPIRE) showed that in their cohort; children who were obese or overweight had their first AP episode and diagnosis of CP at a later age and were less likely to be diagnosed with CP than children who were underweight or normal weight [18].…”
Section: Effect Of Obesity On Pediatric Acute Recurrent Pancreatitis ...mentioning
confidence: 99%
“…Recent studies of ivacaftor with or without lumacaftor contradicted the assertion that exocrine pancreatic insufficiency is irreversible in CF children [ 143 , 144 , 145 ]. However, while pancreatic function improved, as evidenced by the increased fecal elastase-1 concentration and decreased immunoreactive trypsinogen levels, some studies reported an increase in pancreatitis episodes, resembling the phenotype of pancreatic-sufficient CF patients [ 143 , 144 ]. However, in pancreatic-sufficient CF adults, CFTR modulator therapy reduced the risk and frequency of RAP [ 146 , 147 ].…”
Section: Cftr Modulatorsmentioning
confidence: 99%